Art, touch and meaning making: an analysis of multisensory interpretation in the museum. (2nd January 2019) - Christidou, Dimitra; Pierroux, Palmyre
ABSTRACT: This paper presents a multisensory perspective on art interpretation, with a focus on touch as interpretive resource. The context for the study was an art museum exhibition curated to allow touch-based interactions with modernist sculptures. In the first part of the study, visitors' interactions with the sculptures were analysed to identify 'sensing patterns.' In the second part of the study, data were collected from consecutively staged interpretation conditions: perception only, and perception and touch. An analysis of the interactions of one group illustrates the potential of touch as interpretive resource. The study shows how real and vicarious touch introduce a new realm of communicative and interpretive resources that function as sources of information, to confirm or counter visual observations, and in discernments of the sculptures' shape, texture, substance, and their creation process. We conclude by reflecting on the implications of the findings for curatorial and exhibition practices.